Maintenance Management Of Mentilin (Cephalophacus bancanus bancanus) In Captivity In Alobi PPS As A Means Of Exsitu Conservation - Nurzaidah Putri Dalimunthe; Randi Syafutra; Sujadi Priyansah (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
Conservation is one of the efforts that can be made to prevent the decline in the population of Mentilin (Chephalophacus bancanus bancanus) and maintain its existence in nature so that the population is not disturbed. PPS Alobi is an animal rehabilitation center that plays a role in ex-situ conservation efforts for wild animals, so it must have the capacity to realize the ideals of conserving wild animals while ensuring the welfare of these animals in captivity. This research aims to determine the management of keeping mentilin (Cephalophacus bancanus bancanus) in captivity at the Alobi PPS as a means of ex-situ conservation of wild animals. The research was conducted using a survey approach, open and closed interviews, and questionnaires. Mentilin (Cephalopachus bancanus bancanus) maintenance management at PPS Alobi based on drum management parameters adopts an outdoor cage concept. It is built based on the natural needs of mentilin (Chephalophacus bancanus bancanus), and there is environmental enrichment for mentilin activities. Feed management operational standard feed management includes feeding based on the type and amount of feed as well as the frequency of feeding. Health management carries out animal health checks when the animals enter the Alobi PPS, followed by routine checks on the animals. Intensive care for animals that are sick or in unhealthy conditions means the frequency of administration of medicines and vitamins will be more intensive. Animal Health Management is to determine the animal's condition to be released back into its habitat and is supported based on knowledge of Mentilin primate animal conservation. Keywords: Mentilin (Cephalophacus bancanus bancanus), Exsitu conservasi mentilin, Maintenance management mentilin.